Children and Adults Tai Chi Study (CF-CATS2): a randomised controlled feasibility study comparing internet-delivered with face-to-face Tai Chi lessons in cystic fibrosis - Siobhán B. Carr; Patricia Ronan; Ava Lorenc; Awais Mian; Susan L. Madge; Nicola Robinson (ERJ Open Research, 2018)
Virtual healthcare is fast entering medical practice. Research into the feasibility of using it to teach treatment regimens such as exercise has not been explored. Maintaining an exercise regime can be difficult in cystic fibrosis: group classes risk potential infection, yet motivation is hard to maintain when alone. Tai Chi is a low-impact exercise and involves gentle, demanding movements. This study aimed to assess the feasibility, safety and acceptability of learning Tai Chi via an internet-based approach and compared patient-reported outcomes. Children and adults with cystic fibrosis were recruited to a randomised, comparative effectiveness trial. Participants learnt eight Tai Chi movements; teaching was delivered in eight lessons over 3 months: delivered either via the internet or face-to-face. Assessments were at 3-monthly intervals over 9 months. Outcomes included health status, quality of life, sleep, mindfulness and instructor-led questions. 40 adults and children completed the eight sets of Tai Chi lessons. The median age was 22.8 years (range 6.1–51.5 years); 27 patients were female. The cohort comprised 26 adults (aged >16 years), six teenagers and eight children (aged <12 years). The groups were well matched. Feasibility and safety were demonstrated. Participants showed significant improvements in self-reported sleep, cough (both daytime and night-time), stomach ache and breathing. No differences in lung function, health status, quality of life, sleep or mindfulness was shown before or after completing the lessons. Tai Chi was safe and well tolerated; it was feasible to deliver individual lessons via the internet, reducing concerns regarding cross-infection, and appeared to improve self-reported symptoms.